The development stage of Xiamen City and related environment evolution - Tianhai Zhang; Lina Tang; Yanhua Wen; Chenxing Wang (Journal of Environmental Engineering and Landscape Management, 2022)
A model of environmental evolution of cities, especially in East Asia, is said to follow four stages. The pathways to the fourth stage of eco-city are not always clear, but need to be contextual. This research extended the original stage model of environmental evolution to describe urban development and its impact on the environment, especially integrated a model comprise of density, mix and accessibility (DMA) for urbanization and applied Ecological Footprint (EF) concept for pressure on eco-environment. The research analyzed the Xiamen City in China through the first three stages in order to gain insights how the city might be able to hasten its transition to the fourth stage of an eco-city. As expected, the development of Xiamen City and its environmental impacts has very obvious stage characteristic. Before 2010, Xiamen City got through a long time of Stage I (poverty stage); and in the period of 2010 to 2019, Xiamen experienced the Stage II (industrial pollution stage) and Stage III (mass consumption stage) crossly. The new built-up land in the decade of 2000–2010 is much larger than the previous 10 years from 1989 to 2000, 5 times more. Meanwhile, compared with 1980–1995, the ecological deficit also enlarged greatly in period of 1995–2010. Considering up to 2019 Xiamen still has large amount of energy consumption and high level output of industry solid waste, Xiamen should take measures of adjusting the industrial structure, promoting the green industry and planning the urban growth boundary to achieve the eco-city stage.